ANSWERS
• f(g(x)) = sqrt(x² + 9) + 8
,
• g(f(x)) = x + 16sqrt(x) + 73
Step-by-step explanation
To find the composition f(g(x)), we have to replace x with g(x) in the function f(x),
![f(g)=√(g(x))+8=√(x^2+9)+8](https://img.qammunity.org/2023/formulas/mathematics/college/nlxzjreuqen5tky5j7tyon1ugf1yk971g3.png)
This function is in its simplest form.
To find the composition g(f(x)), we have to replace x with f(x) in the function g(x),
![g(f)=f^2+9=(√(x)+8)^2+9](https://img.qammunity.org/2023/formulas/mathematics/college/8uh656lzjp8llf8qwx53uq52kf7a8uomnm.png)
We can simplify this by expanding the binomial squared,
![g(f(x))=(√(x))^2+16√(x)+64+9=x+16√(x)+73](https://img.qammunity.org/2023/formulas/mathematics/college/c66i0v1z4ulv5udym1flm1zmxrmkebevi4.png)
Hence, the two compositions are:
• f(g(x)) = sqrt(x² + 9) + 8
,
• g(f(x)) = x + 16sqrt(x) + 73